Equine Strongylidae and other parasitic nematodes described by Arthur Looss during 1895–1911 in the collections of the Swedish Museum of Natural History - Kuzmina, Tetiana; Holovachov, Oleksandr (Zootaxa, 2023)
Prof. Arthur Looss (1861–1923) was a prolific German parasitologist, who, among other things, authored descriptions of 22 new species of nematodes and 115 new species of trematodes. After his death, his collection (including type material) was split between several institutions: Smithsonian National Museum of Natural History in Washington (USA), Natural History Museum in Berlin and the Natural History Museum in Leipzig (Germany), Gothenburg Museum of Natural History and Swedish Museum of Natural History (Sweden). Here we revise all type specimens of nematodes from the A. Looss collection that are currently preserved in the Swedish Museum of Natural History (Strongylus subtilis, Sclerostomum edentatum, S. vulgare, Cyathostomum labratum, C. coronatum, C. bicoronatum, C. calicatum, C. alveatum, C. catinatum, C. nassatum, C. radiatum, C. elongatum, C. auriculatum, Triodontus minor, T. serratus, C. labiatum and Uncinaria polaris), designate and describe lectotypes wherever deemed necessary and provide catalogue access numbers to all type materials. We also revise all notes and drawings associated with new species that A. Looss described and provide previously unpublished pencilled sketches and ink print-ready drawings of some of these species (Strongylus subtilis, Cyathostomum poculatum, C. radiatum, C. elongatum, C. calicatum, C. auriculatum, Triodontus serratus, Trichostrongylus vitrinus and possibly Necator africanus).